Syntactic Sources of Adjectives in Mandarin Chinese - Liu Feng-hsi (Studies in Chinese Linguistics, 2016)
Cinque (2010, 2014) shows that in English and Italian, adjectives have two syntactic sources, each with different interpretive properties; one source corresponding to predicative adjectives; the other to non-predicative adjectives. This study examines adjectives in Mandarin Chinese with the goal of finding out whether Chinese displays the same pattern. The data shows that Chinese behaves similarly to English and Italian; adjectives that are derived from relative clauses are semantically different from those that directly modify nouns. In addition, Chinese displays the correspondence that predicative adjectives are derived from reduced RC, while nonpredicative adjectives participate in direct modification. However, this parallelism is only possible if we modify the line drawn between “predicative” and “nonpredicative” assumed by Chinese grammarians.